2023
DOI: 10.1097/ms9.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

The study of human monkeypox disease in 2022 using the epidemic models: herd immunity and the basic reproduction number case

Abstract: As of May 2022, a new outbreak of the human monkeypox (MPOX) disease appeared in multiple countries, where the 2022 human MPOX disease spread to more than 109 cases, excluding the suspected cases up to the end of 2022. The deaths of the 2022 human MPOX exceeded 200 cases up to the same date. The human MPOX is not a new disease, this disease was once endemic in some countries on the African continent. Despite this, this disease began to spread in a number of countries around the world in 2022. The first case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Firstly, our simulation results showed that the diagnosis rate, and recovery rate to be 2.73, which is similar to previous research results. 5,[28][29][30] An R 0 value greater than 1 indicates that the disease is still in an uncontrollable state. 31 Compared to previous monkeypox outbreaks in the United States, the 2022 outbreak spread more widely, with more complex transmission pathways and greater difficulty in prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, our simulation results showed that the diagnosis rate, and recovery rate to be 2.73, which is similar to previous research results. 5,[28][29][30] An R 0 value greater than 1 indicates that the disease is still in an uncontrollable state. 31 Compared to previous monkeypox outbreaks in the United States, the 2022 outbreak spread more widely, with more complex transmission pathways and greater difficulty in prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…We further include the current global trend as a function of time for 2022, as shown in Figure 4b. We next go through current modelling literature on the 2022 epidemic, and how modelling is bringing further mechanistic insight into mpox dynamics.
Figure 4. (a) Schematic of basic SIR model with standard incidence, similar as used to model mpox dynamics for the 2022 pandemic [50, 59]. (b) Global reported mpox cases as a function of weeks for the year 2022.
…”
Section: Population-level Epidemiological Modelsmentioning
confidence: 99%
“…4 Another explanation for the drastic reduction of new MPXV diagnoses can be related to herd immunity induced by natural infection. A recent analysis 5 affirms that about 22% of the total susceptible population has to be immunized in an effective way to prevent the spreading of the MPXV, F I G U R E 1 Larger, partially scratched, umbilicated, vesiculo-pustular lesion and several smaller satellite pustules at the pubis and base of the patient's penis (a). Dermoscopy of the larger lesion shows an easily bleeding excoriation, with discontinuous white peripheral halo and perilesional erythema (b), while dermoscopy of one of the smaller satellite pustules revealed a whitish structureless area, with a brownish central depression (c).…”
Section: E T T E R T O T H E E D I T O R the End Of The Monkeypox Eme...mentioning
confidence: 99%